2003
DOI: 10.1046/j.1365-2044.2003.03077.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Outreach team on re‐admissions to a critical care unit

Abstract: Summary Re‐admissions have been cited as a measure of critical care quality and outreach teams have recently been introduced to improve critical care delivery. The aim of this study was to examine whether the number, causes and sequence of re‐admissions to critical care altered as a result of the introduction of an outreach team. Re‐admissions between April 2000 and November 2001 were examined. The reasons for re‐admission were classified as (i) same pathology or disease process; (ii) new, but related, patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 14 publications
1
28
2
Order By: Relevance
“…A recent study could detect no change in patterns of readmission after the introduction of a critical care outreach team 16. It is difficult to extrapolate from the report if the operational policy was similar to that described in our study, and although the setting seems similar, a far larger sample was examined.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A recent study could detect no change in patterns of readmission after the introduction of a critical care outreach team 16. It is difficult to extrapolate from the report if the operational policy was similar to that described in our study, and although the setting seems similar, a far larger sample was examined.…”
Section: Discussioncontrasting
confidence: 51%
“…Our small sample size increased the risk of a type 2 error, which is much smaller than those used to test the effectiveness of medical emergency teams or the effect on readmission rates 8 9 16. If the innovation described here had not been introduced so hastily, owing to political imperative, we could have conducted a prospective randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…88 Current Canadian guidelines are evolving for triage and the use of acuity scales; future adjustments will be required to better detect sepsis in its early stages. 89 From a therapeutic perspective, 90 Hillman 91 and others [92][93][94][95][96][97][98][99][100][101][102] examined the effects of an in-hospital medical emergency team using early identifiers of the high-risk patient. These teams of intensive-care nurses and physicians were mobilized when specified alterations in airway, breathing, circulation and neurologic status were met.…”
Section: The Clinical Link Identification Of the High-risk Patientmentioning
confidence: 99%
“…50,56 Most critical care outreach models use patient mortality, critical care readmission rates from the general care area, length of stay, and patient/caregiver satisfaction as measurements of effectiveness. 1,[48][49][50][51][52][53]56,57 Collectively, studies have demonstrated that patients experienced improved outcomes after implementation of a critical care outreach program; following implementation, patients experienced decreased risk of readmission to the critical care unit 49 and/or shorter stays after readmission. 49,50,52,54,56 In contrast, several studies 51,53,56,58 did not show statistically significant alterations in readmission rates, hospital length of stay, patient anxiety, or hospital survival after implementation of outreach services.…”
Section: Care Delivery Practices Supporting Care Continuitymentioning
confidence: 99%